2023
DOI: 10.1002/lpor.202300464
|View full text |Cite
|
Sign up to set email alerts
|

High‐Power AlGaN‐Based Ultrathin Tunneling Junction Deep Ultraviolet Light‐Emitting Diodes

Shengjun Zhou,
Zhefu Liao,
Ke Sun
et al.

Abstract: Tunnel junctions (TJs) offer a unique approach to utilizing nonequilibrium tunneling injection of holes and have demonstrated potential applications in ultraviolet (UV) emitters. However, high operating voltage caused by the wide bandgap of the III‐nitrides has impeded the further promotion of TJ. Here, 275 nm n+‐Al0.45Ga0.55N/p+‐Al0.5Ga0.5N ultrathin tunnel junction (UTJ) deep‐UV light‐emitting diodes (LEDs) are developed for minimizing the electrical losses and achieve, to the current knowledge, the lowest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…As for Al-rich n-AlGaN, optimizing the epitaxial growth has proven to be effective in reducing its resistivity. In addition, rational design of the epitaxial structure plays an ineligible role for AlGaN-based devices. , It was reported that a graded n-AlGaN contact layer was utilized to obtain a high electron concentration near the interface and achieve better n-contact . Particularly, tunnel junctions have been widely implemented in III-nitride laser diodes and LEDs, which effectively address the issues of high series resistance and DUV light absorption. , Our group recently proposed a recorded ultrathin tunnel junction DUV LED, achieving a low forward voltage of 5.7 V at 300 mA …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for Al-rich n-AlGaN, optimizing the epitaxial growth has proven to be effective in reducing its resistivity. In addition, rational design of the epitaxial structure plays an ineligible role for AlGaN-based devices. , It was reported that a graded n-AlGaN contact layer was utilized to obtain a high electron concentration near the interface and achieve better n-contact . Particularly, tunnel junctions have been widely implemented in III-nitride laser diodes and LEDs, which effectively address the issues of high series resistance and DUV light absorption. , Our group recently proposed a recorded ultrathin tunnel junction DUV LED, achieving a low forward voltage of 5.7 V at 300 mA …”
Section: Introductionmentioning
confidence: 99%
“…45,46 Our group recently proposed a recorded ultrathin tunnel junction DUV LED, achieving a low forward voltage of 5.7 V at 300 mA. 47 In the mesa definition process, etching damages, resulting from the plasma etching, generally act as deep-level compensation centers in Al-rich n-AlGaN. This increases the Schottky barrier height at the metal-AlGaN interface and raises the difficulty in forming ohmic contact.…”
Section: Introductionmentioning
confidence: 99%
“…The low EQEs are directly linked to the inherent material properties of high‐Al‐composition AlGaN, which result in poor internal quantum efficiency (IQE) and poor light extraction efficiency (LEE). [ 1,7 ] The former issue is mainly attributed to high dislocation density, [ 8–10 ] inadequate hole injection, [ 11–13 ] high electron overflow, [ 14 ] and the strong quantum‐confined Stark effect (QCSE) in multiple quantum wells (MQWs). [ 15,16 ] The latter issue primarily arises from significant UV light absorption by the p‐type GaN contact layer, severe light trapping due to strong total internal reflection (TIR), and the unique optical polarization of strong transverse‐magnetic (TM) polarized emission.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial efforts have been proposed to enhance LEEs of the DUV-LEDs, mainly by reducing absorption of materials and by breaking boundary conditions at the air/dielectric interface to attenuate TIR, such as utilizing p-AlGaN with low absorption, [7][8][9] Micro/nano structured LEDs, [10][11][12][13] patterned sapphire substrate (PSS), [14][15][16][17][18] inclined/rough sidewall, [19][20][21] plasmonic nanoparticles, [22][23][24][25] optimized metallic reflector etc. [26][27][28][29] However, the AlGaN-based deep ultraviolet LEDs still suffer from limited LEE with multiple fabrication steps.…”
Section: Introductionmentioning
confidence: 99%